2010
DOI: 10.1007/s12289-010-0858-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of contact tensions during incremental forming of metal composites

Abstract: The realization of light weight design of components with local, load adapted properties is a major goal in the development of new manufacturing and processing methods of metal composite materials. A main challenge in the manufacturing of compounds by forming consists in the realization of the necessary conditions for the initiation of the diffusion process and the generation of metallic bonding. A combination of high contact tensions with specific forming conditions such as temperature distribution and surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…At present, hollow stepped gear shafts are primarily produced by machining processes, which is connected with considerable material losses amounting up to 75% [ 6 ]. Nonetheless, metal forming methods are increasingly widely used to form solid semi-finished products that are then subjected to mechanical working in order to drill holes, remove machining allowance, or form teeth [ 7 , 8 , 9 ]. This way of manufacturing hollow parts ensures reduced material consumption (compared to machining methods) and higher strength properties (material fiber continuity is retained).…”
Section: Introductionmentioning
confidence: 99%
“…At present, hollow stepped gear shafts are primarily produced by machining processes, which is connected with considerable material losses amounting up to 75% [ 6 ]. Nonetheless, metal forming methods are increasingly widely used to form solid semi-finished products that are then subjected to mechanical working in order to drill holes, remove machining allowance, or form teeth [ 7 , 8 , 9 ]. This way of manufacturing hollow parts ensures reduced material consumption (compared to machining methods) and higher strength properties (material fiber continuity is retained).…”
Section: Introductionmentioning
confidence: 99%
“…Neugebauer et al [16] performed microstructural studies on incrementally formed magnesium -aluminium composite. It was found that a homogeneous interface was formed between under the given test condition.…”
Section: Introductionmentioning
confidence: 99%